Charakterystyka chemiczna wód powierzchniowych zlewni Potoku Dupniańskiego oraz Olzy w Beskidzie Śląskim = The characteristic of surface water of Potok Dupniański and Olza drainage area in Beskid Śląski - Małek, Stanisław; Gawęda, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Presented paper contain difference in chosen physic-chemical water parameters between inflow (Potok Dupniański - forest catchment) and outflow (Olza river - agricultural and urban carchment). The stream water quality, beside the snow melting period is higher. The main and determining element for water classifies is their reaction. Waters from Olza river are of pure quality, which is the effect of the inorganic nitric form.
Keywords: 3 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zrównoważona gospodarka zasobami naturalnymi" (24-25.06.2004)